Ultra-thermostable soy protein particles prepared by combining preheating treatment with slightly alkaline pH. Issue 17 (4th August 2022) - Wei, Yixue; Ren, Chao; Cai, Wenqiang; Xu, Xianbing; Wang, Zhenyu; Du, Ming; Wu, Chao
Abstract : Ultra-heat-stable soy protein particles were successfully obtained by combining a preheating treatment with slightly alkaline pH, and suspensions of these proteins remained in the fluid state at protein concentrations as high as 20% (w/v) after the reheating treatment. Abstract : The development of beverages with high protein concentrations has received considerable interest. Nevertheless, the unwanted protein aggregation and gelation of proteins caused by the pasteurization process are currently posing a significant obstacle. Herein, we describe a facile but robust approach to enhance the heat stability of soy proteins (SPs) by preheating at alkaline pH values. When the modified SPs were reheated at a concentration of 2% (w/v), the anti-aggregation properties of the modified SPs were confirmed without any further increase in the size of the particles. Even at concentrations as high as 20% (w/v), the modified protein suspensions preserved their flowability when reheated, whereas the control sample had already gelled at 10% (w/v) concentration. The fluorescence and circular dichroism (CD) spectra indicated that the structures of the modified SPs unfolded and their conformational integrity was diminished after modification. These changes contributed to the reduced unfolding of soy protein and the decreased exposure of active sites during reheating, which inhibited the cross-linking between soy protein molecules during reheating. Meanwhile, the increased surface charge also inhibited the secondary aggregation behavior, improving the thermal stability of protein particles. These findings show that preheating in combination with alkaline pH can be successfully applied to improve the thermal stability of soy proteins, providing a feasible technique and essential insights into the application of soy proteins in protein-enriched liquid systems.